Entropy effects in conformational distribution and conformationally dependent UV-induced photolysis of serine monomer isolated in solid argon - Jarmelo, S. (2006)
Monomeric serine can be trapped in low temperature argon matrices in different conformers, which can be classified in three groups (A, B, C) accordingly to the main intramolecular interaction they exhibit: A (OHA...N hydrogen bond), B (OHC...N) and C (OHA...O) (subscripts A and C stand for alcohol and carboxylic group, respectively). The OHC...N intramolecular interaction found in B-type conformers is considerably stronger than both the OHA...N and OHA...O hydrogen bonds, and leads to reduce the abundance of B-type form relatively to A and C forms at high temperatures due to entropy effects. When submitted to UV irradiation ([lambda]>200 nm), the main observed photoprocess is decarboxylation, leading to production of CO2 and ethanolamine. A less important photochemical process is also observed, where the compound undergoes decarbonylation, with formation of CO, H2O and acetamide. The two observed photoprocesses were found to be dependent on the conformation assumed by the reactant molecule, with A- and C-type conformers of serine undergoing decarboxylation and B-type conformers decarbonylation.